2012
DOI: 10.1104/pp.112.196733
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin Activity of cis-Zeatin and Phenotypic Alterations Induced by Overexpression of Putative cis-Zeatin-O-glucosyltransferase in Rice      

Abstract: cis-Zeatin (cZ) is generally regarded as a cytokinin with little or no activity, compared with the highly active trans-zeatin (tZ). Although recent studies suggested possible roles for cZ, its physiological significance remains unclear. In our studies with rice (Oryza sativa), cZ inhibited seminal root elongation and up-regulated cytokinin-inducible genes, and its activities were comparable to those of tZ. Tracer experiments showed that exogenously supplied cZ-riboside was mainly converted into cZ derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
132
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(146 citation statements)
references
References 74 publications
6
132
0
2
Order By: Relevance
“…This finding suggested that cytokinin levels or signaling might decrease in OsNPR1-OX plants compared with wild-type plants. In fact, cytokinindeficient mutants displayed increased root mass and branching but also shorter stature, thinner stems, narrower leaves, and smaller meristems compared with wild-type plants (Werner et al, 2003;Pineda Rodo et al, 2008;Kudo et al, 2012). Based on the OsNPR1-OX phenotypes of decreased root system and branching (Fig.…”
Section: Osnpr1 Overexpression Alters the Expression Of Hormone-relatmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding suggested that cytokinin levels or signaling might decrease in OsNPR1-OX plants compared with wild-type plants. In fact, cytokinindeficient mutants displayed increased root mass and branching but also shorter stature, thinner stems, narrower leaves, and smaller meristems compared with wild-type plants (Werner et al, 2003;Pineda Rodo et al, 2008;Kudo et al, 2012). Based on the OsNPR1-OX phenotypes of decreased root system and branching (Fig.…”
Section: Osnpr1 Overexpression Alters the Expression Of Hormone-relatmentioning
confidence: 98%
“…Five differentially expressed genes related to cytokinin, including two putative cytokinin-O-glucosyl transferase genes (Os02g51930 and Os06g11720; Kawahara et al, 2013), were up-regulated. These genes encode enzymes that can convert active cytokinin to its O-glucoside (Pineda Rodo et al, 2008;Kudo et al, 2012). The other three cytokinin response genes (Os02g35180, Os04g36070, and Os11g04720; Jain et al, 2006b; Kawahara et al, 2013) were downregulated.…”
Section: Osnpr1 Overexpression Alters the Expression Of Hormone-relatmentioning
confidence: 99%
“…14 Nevertheless, the suppression of infection symptoms by cZ was clearly shown, indicating a role of cZ in plant immunity, which could be even more important in plants responding stronger to cZ compared with tobacco such as rice. 10 Higher levels of cZ than used in this study (maybe in combination with other CKs) could additionally have an impact on defense reactions or a stronger effect on plant fitness, which provides more time for defense reactions to efficiently act directly against the pathogen. The restriction of Pst proliferation through tZ appeared to be less distinct than reported for kinetin, while the suppression of symptoms seemed to be even stronger.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] Since various phytopathogens such as Rhodococcus fascians, 12 Colletotrichum graminicola 13 or Magnaporthe oryzae 8 are capable of producing and modulating cZ-type CKs at infection sites, also a potential impact of cZ on plant immunity must be considered. Here, we comparatively study the differential impact of cZ and tZ treatment on tobacco-Pseudomonas syringae pv tabaci (Pst) interaction, a well-established pathosystem to analyze CK effects on plant immunity.…”
mentioning
confidence: 99%
“…First, reference genes must show an expression level which is high enough to be quantified easily, or at least without difficulty, in applications, particularly RT-qPCR. To determine a practical threshold to evaluate the ease of quantification, distributions of FPKM values were investigated in 16 genes that have been practically used in RTqPCR as reference genes by researchers (Abiko et al, 2005;Benschop et al, 2007;Papdi et al, 2008;Streitner et al, 2008;Li et al, 2009;Li et al, 2010;Fontaine et al, 2012;Kudo et al, 2012;Zhang et al, 2013;Wang et al, 2014;Yin et al, 2014;Gonzalez-Cabanelas et al, 2015;Kamada-Nobusada et al, 2015;Patil et al, 2015;Zhai et al, 2015). In 15 of the 16 genes, the 25th percentile of the FPKM values was above 10; the exception was the Arabidopsis PPR gene, all of whose FPKM values were below 10 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%